Eligibility and Awareness Regarding Metabolic Surgery in Patients With Type 2 Diabetes Mellitus in the Real-World Clinical Setting; Estimate of Possible Diabetes Remission - Koliaki, Chrysi; Tzeravini, Evangelia; Papachristoforou, Eleftheria; Severi, Ioanna; El Deik, Elina; Karaolia, Melina; Noutsou, Marina; Thanopoulou, Anastasia; Kountouri, Aikaterini; Balampanis, Konstantinos; Lambadiari, Vaia; Tentolouris, Nicholas; et al. (Frontiers in Endocrinology, 2020)
Despite high-quality evidence highlighting metabolic surgery as an effective treatment option for type 2 diabetes mellitus (T2DM), the number of patients receiving bariatric surgery (BS) remains low. Since the introduction of the Diabetes Surgery Summit II (DSS-II) eligibility criteria, data on eligibility rates for BS in T2DM cohorts remain scarce. The aims of the present study were to examine in a real-world clinical setting: (i) what is the percentage of T2DM patients visiting diabetes outpatient clinics who meet the DSS-II eligibility criteria, (ii) how many of these have been informed about the option of BS, and (iii) what are the characteristics associated with eligibility and awareness of BS. Demographic, anthropometric, clinical and socioeconomic data were obtained for all patients with T2DM who were consecutively examined in the outpatient clinics of three large-volume university hospitals (n=1167). A medical registry form was completed to screen for BS eligibility. Patients were considered eligible if the recommendation by DSS-II criteria was either to “consider” or “recommend” BS. Eligible patients were further inquired whether they had ever been informed about the option of BS by their physicians. The advanced DiaRem score (ADRS) was applied to eligible patients to assess their probability of achieving postoperative T2DM remission. A significant percentage of T2DM patients who are routinely assessed in outpatient clinics meet the DSS-II eligibility criteria (15.3%). Eligible patients are younger and more obese, have a shorter T2DM duration, worse glycaemic control and better renal function, compared to non-eligible ones. Among eligible patients, only 39.3% have been medically informed about the option of BS. Informed patients are younger and more severely obese than non-informed ones. A significant percentage of non-informed patients (35%) have an ADRS ≤10, indicating a considerable probability for T2DM remission after BS, and are thus deprived of this opportunity due to lack of appropriate medical counselling. Screening and awareness of BS remain an unmet need in current T2DM management. Future research should focus on intensifying screening for BS eligibility at every medical visit and promoting evidence-based clinical recommendations for patients expected to benefit the most.